(untitled) (Praxis Educativa, 2024)
In this article, we investigate the modes of production and circulation of meaning in the educative practices developed in classroom contexts at the secondary level, in a school in the Autonomous City of Buenos Aires. From the approach of critical sociolinguistics (Codó et al., 2012; Niño Murcia et al., 2020), that articulates the perspectives of ethnographic sociolinguistics and critical discourse analysis, we analyze the interactions developed in a 3rd year Language and Literature course, focusing especially on the teacher’s interventions, with the aim of investigating to what extent her participation opens the space for the production and circulation of meanings that question the established order or, on the contrary, restricts it. In this way, we are interested in determining which pedagogical models underlie these educational practices by characterizing the pedagogical discourse that circulates in the classroom.